Identification and Validation of N6-Methyladenosine-Related Biomarkers for Bladder Cancer: Implications for Immunotherapy - Deng, Hongyu; Tang, Faqing; Zhou, Ming; Shan, Dongyong; Chen, Xingyu; Cao, Ke (Frontiers in Oncology, 2022)
N6-methyladenosine (m6A) has emerged as one of the most important modifications of RNA. Based on the expression of 23 different modes of m6A regulatory factors, we identified three different m6A modification patterns in bladder cancer. The effects of the three different modes of m6A modification on clinicopathological characteristics, immune cell infiltration levels and expression levels of immune checkpoint genes were comprehensively analyzed. In addition, the effects of different modes of m6A modification on the therapeutic efficacy of anti-PD-L1 immunotherapy (atezolizumab) are also discussed. Our results confirm that m6A methylation plays an important role in immune cell recruitment in the tumor microenvironment of bladder cancer, which influences the efficacy of anti-PD-L1 therapy for bladder cancer. We further confirmed the important role of FTO protein in the biological function of bladder cancer cells by performing in vitro experiments. FTO functions as an oncogene in bladder cancer cells, and upon FTO knockdown, the level of m6A enzyme activity in bladder cancer cells was significantly increased, apoptosis was increased, and cell proliferation and cell invasion were reduced. In addition, our study also confirmed that K216H and K216E are probably important targets for regulating FTO. We provide new insights into the regulatory pathways of the immune microenvironment and the methylation function of m6A in bladder cancer, which will help in designing novel diagnostic methods, prognostic tools, and therapeutic targets.